Reactant friendly hydrogen evolution interface based on di-anionic MoS2 surface - Zhaoyan Luo (Nature Portfolio, 2020)
H2 energy as an alternative to fossil fuels requires cost-effective catalysts with fast kinetics for splitting water. Here, authors design MoS2 materials with di-anionic surfaces to improve the electrocatalytic H2 evolution activities.